Homicide and economic change: Recent analyses of the Joint Economic Committee report of 1984 - Brenner, M. Harvey (Journal of quantitative criminology, 1986)
The relation between recession and homicide is classic in the United States. This has been affirmed in the 1976 and 1984 Reports to the Joint Economic Committee (JEC) of the United States Congress. Recent analysis confirms the findings reported in both 1976 and 1984 and demonstrates that the influence of recession on homicide is greater than previously estimated. Differences in the 1976 and 1984 findings on homicide are related to differences in the hypotheses tested, as discussed in detail and highlighted in the 1984 report. JEC staff correctly interpreted and reported the 1984 findings. Reproduction of the 1984 homicide equation is straightforward, provided the same data and any of several standard estimation techniques are used. Evidence does not support any of Cook and Zarkin's claims in their critique of the 1984 homicide equation. The JEC report of 1984 used appropriate techniques in the attempt (a) to ensure that influences attributed to economic changes are not actually due to other social factors and (b) to minimize underspecification of models.